The Death awareness and Spiritual Experience of Health Care Workers during Coronavirus Outbreak - ali nobahri; elham fathi; fateme malekshahi beiranvand; abolfazl hatami varzaneh (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: The present study aims to identify the death awareness and spiritual experience of the health care workers in Iran. Methods: Eleven health care workers involved with Coronavirus patients were selected through purposeful sampling and had in-depth semi-structured interviews. Conventional content analysis was utilized to analyze the data. Results: The conventional content analysis revealed four themes: 1- Increasing death awareness 2- Effective spiritual strategies; 3- Effective spiritual beliefs; 4- Pleasant and unpleasant existential experiences. Conclusion: We can conclude that health care workers in dealing with epidemics such as coronavirus as a front-line force need spiritual heath to help themselves and the patients